Assessment of non-formal adult education and training centres’ enabling environments for employment and poverty reduction in Kwazulu-Natal, South Africa - Lombard, A. (Antoinette) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.